The optical polarization variability of the blazar PKS 2155 304 - Peceur, Nicolette (Department of Astronomy, 2024)
Blazars are some of the most energetic and variable objects in the universe. Blazar emission has been detected across the electromagnetic spectrum and exhibits variability on a wide range of timescales, from minutes to years. The observed emission is Doppler boosted and dominated by non-thermal radiation driven by the magnetic field of a relativistic jet. PKS 2155–304 is an archetypal blazar, located in the southern hemisphere. The source is bright and highly variable, displaying both active and quiescent states. In this thesis I make use of optical polarization and multiwavelength observations across roughly 5.5 years to probe the source variability on short (intra-day to daily), intermediate (days to months) and long timescales (months to years). The polarization, as a direct observable of the jet's magnetic field, can help gain insight into the physical processes that underlie the observed emission, while contemporaneous multiwavelength observations can assist in distinguishing between dierent emission models. I investigated the short term variability of PKS 2155–304 by using optical polarization measurements recorded over a 3 day period during a period of enhanced gamma-ray activity. The observations revealed, for the first time, evidence of quasiperiodic oscillations in the optical polarization of a blazar. A periodogram analysis of the polarized flux revealed the existence of two periodic components at ≥ 13 minutes and ≥ 30 minutes. The oscillations can be explained by turbulence behind a relativistic shock traversing a jet containing quasi-helical structures in magnetic field or electron density. To study the intermediate timescale brightness variations of the source I analysed its optical polarization and BVRJ multiband light curves during a prominent optical flare in 2010. The flare evolved over roughly 4 months with a flux doubling time of ≥ 11 days. A comparison of the polarization angle and photometric flux revealed the existence of two distinct states at low and high flux. Below 18 mJy, no clear relationship is seen between the polarization angle and flux, while there is a positive correlation above 18 mJy. I performed a photopolarimetric analysis of the high flux state, which showed that it can be attributed to a variable component with a power-law radiation spectrum of index ≠1.12 and a polarization degree of 13.3%. I then applied a shock-in-jet model to the observations, which showed that the observed variability can be attributed to a nearly edge-on shock. Within the shock-in-jet model, I derived estimates for the magnetic field (0.06 G), Doppler factor (22.3) and viewing angle of the jet (2.6¶). Lastly, I performed an investigation of the long term variability of the blazar by analysing roughly 5.5 years of radio, optical, optical polarization, X≠ray and “≠ray measurements. Using a correlation analysis, I found that the optical, X≠ray and high energy light curves were consistent with zero lag, while the radio light curve lagged behind the higher energy emission by ≥ 46 days. The lag between the radio and higher energy light curves is consistent with opacity eects due to synchrotron emission. The nearly zero lag between the synchrotron (optical and X≠ray) and Inverse Compton (high energy) emission components indicates that the same electron population is responsible for the emission. When computing the temporal structure functions of the multiband light curves, I found that the multiwavelength emission can be described by a power-law spectral density function, with an index of –1.5 for the radio, –1.3 for the optical, –0.6 for X≠rays and –1.0 at high energies. A break timescale is present for the optical and X≠ray band, below which the structure function is characterised by white noise. The structure functions also indicate the existence of periodic outbursts roughly every 1.8 years. My analysis of the multiband photometric fluxes showed that the optical emission is well-described by a variable component with a power-law radiation spectrum of index ≠1.13, consistent with synchrotron emission. For a power law electron distribution, the optically thin synchrotron emission implies an energy spectrum with an index of ≠3.26 for the electrons. Finally, the long term optical polarization supports the existence of a constant polarization component with a polarization degree of 3.4% and a polarization angle of 76¶. The results of my analysis indicate that the emission from PKS 2155–304 is composed of two components, a persistent component with low polarization degree and a magnetic field that lies roughly parallel to the direction of the jet, and a variable component with a constant power-law radiation spectral index and high polarization degree. The variable emission component is consistent with a relativistic shock propagating in the jet on timescales from day to months, where intraday quasi-periodic oscillations can arise due to turbulence behind the shock. The structure function analysis of the long term behaviour indicates that there is power in the variable component on all time scales down to the break in white noise. However, the variable component undergoes major outbursts roughly every 1.8 years. The constant power-law observed for the variable emission over roughly 5.5 years means that the particles have the same energetics. The nearly zero lag across the dierent energy bands indicates that the same particle population underlies the low and high energy emission, consistent with Synchrotron Self Compton models.